Prawo w umyśle. Kilka uwag o teorii Leona Petrażyckiego w kontekście neurolaw - Próchnicki, Maciej Michał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Pioneering theories of Leon Petrażycki regarding law and emotions have not been popularized in the Western scientific literature. Yet, some authors writing on neurolaw, a new field of interdisciplinary studies, integrating neuroscientific research and legal studies, have proposed strikingly similar ideas regarding the essence of law. In particular, this concerns the idea of law as a mental state, which should be studied scientifically. The main objection to such a theory may be its reductionism. However, this theory could have been enhanced with a social, multi-layered context. Moreover, Petrażyckian idea of emotion as mixed cognitive-conative states, which serve as a main factor of ethical motivation, is nowadays an important point in philosophical-psychological discussions.